Analisis Penerapan Standar Akuntansi Keuangan Entitas Usaha Mikro Kecil dan Menengah (SAK- EMKM) Toko Queen Roti Kecamatan Oebobo Kota Kupang - Maria Marsela Nasrani; Petrus E. De Rozari; Yohanes Demu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the presentation of financial statements based on SAK EMKM at Queen Roti Shop. This research was conducted on MSMEs of Queen Roti Shop located on Jl. Piet A Tallo, Liliba, Oebobo District, Kupang City, East Nusa Tenggara. The type of data of this research is quantitative descriptive using qualitative data related to the implementation of SAK EMKM in financial statements. Data collection uses interviews, documentation, and observation. The results of the study provide an overview that (1) the financial statements of the queen Roti store have a transaction of incoming and outgoing money. When compared to SAK EMKM, financial statements are formed based on Income Statements, Financial Position Statements, and Notes on Financial Statements. (2) The Queen Roti Shop has not used the guidelines in accordance with the SAK EMKM, so the researcher prepared a financial report for the Queen Roti Shop in accordance with the SAK EMKM guidelines.